Islamic Education Quality Standards in Educational Institutions According to Thu'aimah’s Thought - Ansari Ansari; Achmad Muhlis (Ambarsa : Jurnal Pendidikan Islam, 2026)
The implementation of quality standards in Islamic education within educational institutions is a crucial aspect of modern educational management. This study adopts a qualitative approach with a library research method, analysing various relevant sources of literature. The findings reveal that the quality standards of Islamic education, according to Thu’aimah, are holistic and integral, encompassing spiritual, intellectual, moral, and social dimensions. These standards are implemented through stages of planning, implementation, evaluation, and quality control in educational management. The implementation is realized through the formulation of a vision and mission based on Islamic values, the development of an integrative curriculum, the implementation of Islamic-based learning, and continuous and holistic evaluation as a means of improving education quality. This study concludes that the ideas of Thu’aimah have strong relevance to contemporary educational quality management concepts and can serve as a conceptual foundation for managing Islamic educational institutions in a professional, sustainable manner, oriented toward the development of morally upright individuals. For future research, it is recommended to explore the practical challenges and success factors in applying these quality standards across various Islamic educational institutions with diverse cultural and regional contexts.